2016
DOI: 10.5502/ijw.v6i2.557
|View full text |Cite
|
Sign up to set email alerts
|

A study investigating the effects of Mindfulness-Based Strengths Practice (MBSP) on wellbeing

Abstract: Mindfulness practice and character strengths have been determined as being two separate positive psychology interventions (PPIs). However, to date, no programme has researched and investigated the effects of combining these theoretically interlinked practices together, with the aim of enhancing wellbeing from a positive psychology perspective. The current controlled study was designed to establish the effectiveness of an 8-week online mindfulnessbased character strengths practice (MBSP) on wellbeing, for the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 32 publications
3
15
0
2
Order By: Relevance
“…Two comparison studies showed MBSP is superior to the gold-standard mindfulness-based program, Mindfulness-Based Stress Reduction (MBSR), on the workplace outcome of employee performance using supervisory ratings (both fared equally to one another and superior to controls for well-being and stress) (Pang & Ruch, 2019a) and in elevating certain character strengths such as humor (Hofmann et al, 2019). Other empirical studies found MBSP to be superior to controls in boosting flourishing, life satisfaction, engagement, and signature strengths use (Ivtzan, Niemiec, & Briscoe, 2016), as well as showing significant improvements to engagement, health, well-being, and meaning, as well as increases in student retention at the collegiate level (Wingert et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Two comparison studies showed MBSP is superior to the gold-standard mindfulness-based program, Mindfulness-Based Stress Reduction (MBSR), on the workplace outcome of employee performance using supervisory ratings (both fared equally to one another and superior to controls for well-being and stress) (Pang & Ruch, 2019a) and in elevating certain character strengths such as humor (Hofmann et al, 2019). Other empirical studies found MBSP to be superior to controls in boosting flourishing, life satisfaction, engagement, and signature strengths use (Ivtzan, Niemiec, & Briscoe, 2016), as well as showing significant improvements to engagement, health, well-being, and meaning, as well as increases in student retention at the collegiate level (Wingert et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…93 Achtsamkeit ist somit mit Persönlichkeitsentwicklung verbunden. Ivtzan et al (2016). 94 Nehls (2014) Lefebre (2013);Triclot (2013).…”
Section: Ergebnisse: Komponenten Des Subjektiven Wohlbefindensunclassified
“…This eight-week programme applying the principles of mindfulness in the context of positive psychology is about engaging more deeply with life: it helps us to achieve our goals, to cope with problems and to connect deeper with others. One study investigating effects of MBSP on well-being for a general population (Ivtzan, Niemiec & Briscoe, 2016) showed that the experiment group scored higher on well-being and flourishing, and that the programme had a positive impact on well-being.…”
Section: Positive Parentingmentioning
confidence: 99%